Hubungan Pengetahuan, Pekerjaan, dan Dukungan Keluarga Terhadap Kegagalan ASI Ekslusif Di UPTD Puskesmas Pengaringan Kabupaten Oku - Lely Lora; Ahmad Arif; Dewi Ciselia; Habiah Habiah (JUKEJ : Jurnal Kesehatan Jompa, 2023)
Breast milk is the best food for babies. It cannot be replaced with other foods and no food can replace breast milk. The converage of breast feeding babies in OKU Regency in 2018 was 60,7%. in pengaringan primary health care center area in 2021 it was recorded that out of 168 babies there wewe 146 babies who failed to have exclusive breastfeeding (86,9%). the objective of the of implementing exclusive breastfeeding in the UPTD area of pengaringan primary health care center, semidang Aji district, OKU Regency in 2021. this study was quantitative with a cross-sectional design. The population of the study was all mothers who had babies aged more than 6 months, who visited the UPTD Primary health care center of pengaringan, semindang aji sitrict, OKU Regency in february 2022. the sampel of the study was 30 a quistionnaire. The data were analyzed by means of chi -square test formula. The results of with the failure of exclusive breastfeeding with the value of variable of knowledge (p-0.004) and family support (p-0,013). there was no significant relationship between work and exclusive breastfeeding failure with p-value of 0.402. it is expected that the primary health care center be able to increase health counseling related to exclusive breastg=feeding and put up more health information such as posters about exclusive breastfeeding.